2000
DOI: 10.1080/713654906
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase in the utero-vaginal junction of immature and mature ostriches

Abstract: 1. Sperm storage tubules in the ostrich start to develop at an early stage of oviductal growth. Concurrently, membrane-bound carbonic anhydrase was found in the cells of the storage tubules. 2. In mature ostriches the utero-vaginal junction averaged 11.5+/-2.1 cm in length and primary mucosal folds were extremely long and slender. Membrane-bound carbonic anhydrase was present in the cells of the sperm storage tubules. In the non-ciliated cells of the surface epithelium both membrane-bound and cytoplasmic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Seven days later, small bud-like invaginations were found in this region. Similar epithelial invaginations have been found in sexually immature ostriches (Holm et al, 2000) and young nonphotostimulated turkeys (Bakst,'92). Bakst ('88,'92) also detected fully developed SST, containing spermatozoa, in young turkeys with undeveloped ovary and oviduct, suggesting that development of the SST may take place before the maturation of the rest of the oviduct.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Seven days later, small bud-like invaginations were found in this region. Similar epithelial invaginations have been found in sexually immature ostriches (Holm et al, 2000) and young nonphotostimulated turkeys (Bakst,'92). Bakst ('88,'92) also detected fully developed SST, containing spermatozoa, in young turkeys with undeveloped ovary and oviduct, suggesting that development of the SST may take place before the maturation of the rest of the oviduct.…”
Section: Discussionmentioning
confidence: 70%
“…However, this short region, only about 1-2 mm in the quail, shows a very distinct localisation of the enzyme carbonic anhydrase, which cannot be found in the surface epithelium in any other region of the oviduct. Likewise, a similar pattern of carbonic anhydrase has been found in the utero-vaginal junction epithelium of all bird species investigated so far (Holm et al, '96;Holm and Ridderstråle, '98;Holm et al, 2000). The exact role of the enzyme has not yet been established, but it has been suggested that it is involved in regulation of sperm motility by adjusting the luminal pH, because it is know that spermatozoa need to be motile to reach the SST.…”
Section: Discussionmentioning
confidence: 73%
“…The transition between the two regions is abrupt and well demarcated (Bezuidenhout et al, 1995). In the ostrich, SST are present in the vagina in a wide band immediately adjacent to the uterovaginal junction (Bezuidenhout et al, 1995;Groenewald et al, 1996;Holm et al, 2000). The presence of SST demarcates the utero-vaginal junction which is reported to vary between 11.5 cm (Holm et al, 2000) and 20 cm (Bezuidenhout et al, 1995) in length.…”
Section: Sperm Storagementioning
confidence: 89%
“…However, the number of days over which sperm are detected suggests that the ostrich clutch size may be larger than values previously reported, or female ostriches store sperm for up to two clutches. Their long sperm storage duration could have a basis in a relatively large uterovaginal region containing long sperm storage tubules, a storage system resembling that of the turkey (Holm et al, 2000), a species that stores sperm for up to 72 days (Birkhead, 1988). Similarities in the utero-vaginal region between the two species could explain why the rate of sperm loss in the ostrich is similar to that of the turkey (-0.003 per hour log; Wishart, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…On commercial farms, it directly affects profitability because it determines the proportion of fertile eggs laid by each female (Cloete et al, 1998). Fertility of ostrich eggs varies considerably between and within farms (Badley, 1997;Bunter & Graser, 2000) despite a reproductive strategy that should guarantee high fertility through high rates of sperm supply and the presence of sperm storage tubules in the female (Bezuidenhout et al, 1995;Holm et al, 2000;Malecki & Martin, 2003b).…”
Section: Introductionmentioning
confidence: 99%